Bare bones - Reichs, Kathy (London : Random House, 2003)
Forensic anthropologist Tempe Brennan's plans for a long-overdue vacation with her boyfriend are delayed by some mysterious bones, a plane crash, and her daughter's new relationship.
Library Journal
Publisher's Weekly
Wilson's Fiction
Adult
Adult
English
Keywords: Brennan, Temperance (Fictitious character) -- Fiction; Endangered species -- Fiction; Forensic anthropology -- Fiction; Smuggling -- Fiction; Women anthropologists -- Fiction; Brennan, Temperance (Fictional character) -- Fiction; Endangered species -- Fiction; Forensic anthropology -- Fiction; Mystery fiction; Smuggling -- Fiction; Women anthropologists -- Fiction; North Carolina -- Fiction; North Carolina -- Fiction; Mystery fiction